Singing with cicadas - Guo, Rayven Ruifeng (Nanyang Technological University, 2022)
"Singing With Cicadas" is a personal journey that leads to the revelation of my inner self and my internal home. This intimate photographic work expresses my fragility and unease at home, which has a significant impact on my personality and existence. Clearly, I have an external home; it is the place to which I return each evening. But what about my internal home? The place where I can find a sense of belonging and rootedness, where I may feel safe and unburden myself. In this project, I'll investigate and explore my search for the meaning of home, a place where I may feel safe both emotionally and externally.